Research on the segmentation method of a highway landscape corridor zone - Hu, Shengneng; He, Guoqi; Xu, Hongwei (Frontiers in Environmental Science, 2023)
Highway landscape is an important part of highway construction, which plays a role in highway engineering to ensure traffic safety, alleviate visual fatigue, manifest culture, and many other roles. In the actual highway landscape design, the concept of highway landscape planning and design is unclear, the content is confusing, and the design lags behind the main construction of the problem. Different landscape themes should be set for different sections of the road to enable the motorway landscape to play its role, and the reasonable division of the highway landscape paragraph nodes and the determination of different landscape themes are the keys to the problem. This study collects natural and humanistic materials along the highway, arranges and classifies them through the method of cluster analysis, and then divides the highway landscape into paragraphs through the fusion of cluster analysis and node control method; then integrates and refines the landscape resources in the paragraphs to define the theme of the paragraphs; and secondly generates the landscape of the paragraphs based on the theme of the paragraphs, to bring out the regional cultural connotation, and constructs a Highway paragraph landscape theme division process. Finally, based on the survey of the landscape status quo of Zhunxing Highway, the landscape theme division method is applied to verify its scientificity. The research results show that the highway paragraph landscape division method based on the cluster analysis method can effectively reflect the landscape characteristics of different road sections, enrich the road landscape design content, reflect the regional cultural characteristics, reduce the phenomenon of driver fatigue due to the landscape content of a single driving, and protect the traffic safety of the highway. The method can effectively guide the highway landscape paragraph planning and node design, has simple operation, and has strong practicality.